Auswirkungen des Basel II Akkords auf österreichisches KMU - Thomas Heimer; Thomas Köhler (Hochschule für Bankwirtschaft (HfB), 2004)
The paper discusses the impact of the Basel II Accord on the financing of small and medium size enterprises (SME) in Austria. Although the Basel II Accord has not been established yet, the study tries to evaluate the expected impact of the Basel II Accord on SMEs, on the bases of the current financial data of SMEs. The empirical work used the NACE datapool for Austrian SME provided by KMU Forschung Austria. In the datapool, SMEs are defined as companies with a turnover of up to exteuro 100 Mio. In addition to the statistical analysis an empirical data survey has been conducted by Triconsult. The survey focused on the expected impact of the Basel II Accord on SMEs by intermediaries (f.i. consultancies and technology transfer agencies). The results of the study show that most SME and intermediaries are not prepared for the new regulations initiated by Basel II. Accordingly three measures should be taken by policy makers to enhance SMEs capability to adjust to the new requests established by the Basel II Accord: 1. Extension of the information for SMEs on the impact of the Basel II Accord. 2. Companies should be motivated to enlarge indicators that give banks information about their financial development. 3. Measures are required to improve the financial structure of SMEs in Austria.
urn:nbn:de:101:1-2008082541
Keywords: G10; G32; G38; 330; Basel II Accord; Innovation; Finance of Innovation